LOCALIZING THE SUSTAINABLE DEVELOPMENT GOALS THROUGH VOLUNTARY LOCAL REVIEWS IN THE GAMBIA - Jonga, Modou (Fakultas Politik Pemerintahan, 2024)
This paper explores the importance of Voluntary Local Reviews (VLR) in the localization and acceleration of the attainment of a powerful global blueprint to deliver a better future. The paper regard Local voluntary Reviews as accelerators and an inclusive approach for the localization of the 2030 Agenda. According to the 2030 Agenda (A/RES/70/1: Transforming Our World: The 2030 Agenda for Sustainable Development) encourages member states to “conduct regular and inclusive reviews of progress at the national and sub-national levels, which are country-led and country-driven”. The value of VLR in advancing SDG implementation has been increasingly recognized at national and international level. The Paper used documentary sources to gather information relevant to the thematic area. These included journal articles, books, local and regional governments reports. The researcher also examined the VLR pilot reviews in The Gambia supported by the United Nations Department of Economic and Social Affairs (UN DESA) and other relevant partners. The Paper strongly recommends peer-to-peer learning to enrich VLR processes at local level with a view to bolster local action.